Electrochemical responses of carbon fiber microelectrodes to dopamine in vitro and in vivo - Budai, Dénes (Acta Biologica Szegediensis, 2010)
Cylindrical, 7 μm in diameter carbon fiber (CF) microelectrodes were constructed and tested for their responses to dopamine in constant potential amperometry or fast scan cyclic voltammetry (FSCV). Amperometry was carried out in a miniature perfusion chamber whereas background subtracted FSCV was performed both in vitro and in vivo. For calibration performance of the microelectrodes, peak oxidation currents were determined using unmodified carbon tips of varying lengths and plotted against the tip lengths. A very close linear correlation (r = 0.997) was found between the two variables for tip lengths ranging from 25 to 300 μm. Also, a very close linear correlation was found between the oxidation current at a given carbon tip length in response to increasing dopamine concentrations measured by either amperometry or FSCV. In vivo experiments were carried out in the visual cortex of the anaesthetized rat to detect dopamine release in response to visual stimulation. Indeed, background subtracted cyclic voltammograms showed an increase in the current at 0.65 V which is the typical dopamine oxidation potential.